KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DILIHAT DARI METAKOGNISI MATERI BANGUN DATAR SMPN 3 SUNGAI PINYUH - Yanuardi, Yayan; Hartoyo, Agung; Nursangaji, Asep (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to know and describe students mathematic problem solving ability on metacognition ability plane geometry in class VII SMP N 3 Sungai Pinyuh. This research used descriptive method with survey form. The subjects of this research were 25 students of class VII A in SMP N 3 Sungai Pinyuh. Data collection tool used test, questionnaire, and interview. Test given to know students mathematic problem solving ability, questionnaire given to know metacognition ability, and interview given to find out more metacognition ability. The result of this research showed: (1) From 8 students have students mathematic problem solving ability as high category, 1 student as good metacognition ability category, 5 students as medium metacognition ability category, and 2 students as low metacognition ability category; (2) From 5 students have students mathematic problem solving ability as medium category, 3 students as medium metacognition ability category, and 2 students as low metacognition ability category; (3) From 12 students have students mathematic problem solving ability as high category, 4 students as medium metacognition ability category, and 8 students as low metacognition ability category. Keywords: Problem Solving Ability, Metacognition Ability, Plane Geometry